(untitled) - Phùng, Ngọc Kiếm (H., 2000)
NV Truyện và truyện ngắn Việt Nam hiện đại
Keywords: Văn học Việt Nam -- 1945-1975; Truyện ngắn Việt Nam -- 1945-1975; Văn học Cách mạng -- 1945-1975 -- Việt Nam